2011
DOI: 10.1080/15374416.2011.546040
|View full text |Cite
|
Sign up to set email alerts
|

Why Superman Can Wait: Cognitive Self-Transformation in the Delay of Gratification Paradigm

Abstract: We examined middle-class Israeli preschoolers' cognitive self-transformation in the delay of gratification paradigm. In Study 1, 66 un-caped or Superman-caped preschoolers delayed gratification, half with instructions regarding Superman's delay-relevant qualities. Caped children delayed longer, especially when instructed regarding Superman's qualities. In Study 2 with 43 preschoolers, with the respective relevant superhero qualities emphasized (i.e., patient vs. impulsive), Superman-caped children tended to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 35 publications
1
20
0
1
Order By: Relevance
“…Follow‐up studies are needed to isolate effects of self‐distancing versus character competence. As mentioned above, thinking about the positive attributes of an exemplar could have led participants to take on positive characteristics such as working hard (Adam & Galinsky, ; Karniol et al., ), in conjunction with self‐distancing—or maybe even independent of it. What if characters were not powerful exemplars but rather unfamiliar children?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Follow‐up studies are needed to isolate effects of self‐distancing versus character competence. As mentioned above, thinking about the positive attributes of an exemplar could have led participants to take on positive characteristics such as working hard (Adam & Galinsky, ; Karniol et al., ), in conjunction with self‐distancing—or maybe even independent of it. What if characters were not powerful exemplars but rather unfamiliar children?…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also shown that transcending one's self‐immersed point of view can facilitate self‐regulation in preschoolers. Making decisions for another person rather than themselves (Prencipe & Zelazo, ) or impersonating a character (Karniol et al., ) helped preschoolers' to delay gratification. In another recent study, White and Carlson () assessed the effects of varied levels of self‐distancing on children's executive function (EF) performance using the Minnesota Executive Function Scale (Carlson & Zelazo, ).…”
Section: Present Studymentioning
confidence: 99%
“…Some of these studies created distance between the child and a tempting stimulus (e.g., marshmallow) by having the child cognitively transform it into something less appealing and more abstract (e.g., clouds) or by replacing the treats with abstract symbols (Apperly & Carroll, ; Carlson, Davis, & Leach, ; Mischel & Baker, ). Other studies created social distance by asking children to make decisions to delay gratification (or not) from a third‐person perspective instead of from a first‐person perspective or by thinking about someone who would be good at the task (e.g., Superman) (Prencipe & Zelazo, ; Karniol et al ., ). In each case, creating distance from the stimuli or the self resulted in greater self‐control.…”
Section: Introductionmentioning
confidence: 97%
“…Most studies that have successfully manipulated delay of gratification have involved the provision of specific techniques to delay, such as providing children task‐specific cognitive strategies (e.g., look away from the marshmallow, Mischel & Ebbesen, ; ‘imagine the marshmallow as a cloud’; Mischel & Baker, ). Other work suggests that providing children with a personal or group identity associated with self‐control can increase delay (e.g., a Superman cape, Doebel & Munakata, ; Karniol et al, ; Toner, Moore, & Emmons, ; see White & Carlson, ; White et al, for similar examples). Instead, we used a model to represent the idea that exerting self‐control can be energizing.…”
Section: Introductionmentioning
confidence: 99%